Water-based plastic-replacing gold sand gloss oil and preparation method thereof

By using hydrophoneic polyurethane resin, water -based acrylic resin, etc., water -based plastic gold sand optical oils, solving the problem of flammable and explosive and harmful to the human body in existing technologies, and realized safe and reliable use and good optical oil coating performance Essence

CN119371886APending Publication Date: 2025-01-28杭州顶正包材有限公司

Patent Information

Application Number
CN202411509529.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing sterilized varnish contains flammable and explosive isobutanol and harmful ingredients to the human body, which poses safety hazards.

Method used

Using water -based polyurethane resin, hydraulic acrylic resin, golden sand powder, water, water -based polypropylene wax, and polyether modified organic silicon surface activated agent, water -based plastic gold sand optical oil to avoid using flammable and explosive ingredients, and re -entered And decentralized treatment to ensure the bending, abrasion resistance and water resistance of the optical oil coating.

Benefits of technology

The water -based water -based gold sand optical oil that does not contain flammable and explosive ingredients and the harmful ingredients to the human body ensures the safety and reliability of the use and preparation process, and improves the performance of the light oil coating.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses water-based plastic-replacing gold sand gloss oil, which is prepared from 30 to 40 parts of water-based polyurethane resin, 10 to 30 parts of water-based acrylic resin, 10 to 20 parts of gold sand powder, 10 to 20 parts of water, 3 to 5 parts of water-based polypropylene wax and 0.5 to 3 parts of polyether modified organic silicon surfactant. The water-based paint is composed of the water-based polyurethane resin, the water-based acrylic resin, the gold sand powder, the water, the water-based polypropylene wax and the polyether modified organosilicon surfactant, and the whole components do not contain flammable and combustible components such as isobutanol and do not contain components harmful to human bodies, so that the water-based paint is relatively safe and reliable during use and preparation. The invention further discloses a preparation method of the water-based plastic-replacing gold sand gloss oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of printing ink, and in particular to a water-based plastic-replacing varnish and a preparation method thereof. Background Art

[0002] Plastic replacement gold sand varnish is a commonly used paint at present. Patent announcement document CN101725082B discloses a varnish paint. This varnish paint can be formed by adding gold sand powder when applying it. This varnish paint is made of acrylic emulsion, acrylic resin, polyethylene wax, isobutyl alcohol and polytetrafluoroethylene wax. Since isobutyl alcohol is used in this paint, there is a risk of deflagration during preparation. Secondly, this paint has certain harm to the human nervous system when used. Summary of the invention

[0003] In view of the above problems, the present invention proposes a water-based plastic replacement gold sand polish, which is composed of water-based polyurethane resin, water-based acrylic resin, gold sand powder, water, water-based polypropylene wax and polyether modified silicone surfactant. The entire component does not contain flammable and explosive ingredients such as isobutyl alcohol, and does not contain ingredients harmful to the human body. It is relatively safe and reliable when used and prepared.

[0004] The technical solution adopted by the present invention is as follows:

[0005] A water-based plastic replacement polish comprises 30-40 parts of water-based polyurethane resin, 10-30 parts of water-based acrylic resin, 10-20 parts of plastic powder, 10-20 parts of water, 3-5 parts of water-based polypropylene wax, and 0.5-3 parts of polyether-modified organic silicon surfactant.

[0006] This water-based plastic replacement polish is composed of water-based polyurethane resin, water-based acrylic resin, plastic powder, water, water-based polypropylene wax and polyether modified silicone surfactant. The entire component does not contain flammable and explosive ingredients such as isobutanol, and does not contain ingredients harmful to the human body. It is relatively safe and reliable during use and preparation.

[0007] Water-based acrylic resin has a high glass transition temperature and high hardness, but poor toughness. In order to ensure that the varnish has good toughness after solidification, the varnish disclosed in the present application is compounded with a water-based polyurethane resin and a water-based acrylic resin. The varnish coating obtained by the final ratio has good bending resistance, wear resistance and water resistance after solidification.

[0008] In this varnish component, water-based polypropylene wax reduces the friction coefficient and improves the wear resistance, and increases the viscosity of the system to prevent the gold sand powder from settling and failing. The addition of water-based polypropylene wax can ensure that the varnish coating has good gloss and wear resistance after application. At the same time, since the gold sand powder can be prevented from settling, it can be ensured that the gold sand powder can be evenly distributed in the entire varnish component, and the gold sand powder can be prevented from being deposited on the surface of the paper after the varnish is applied to the paper. This can avoid the presence of a gold sand layer between the paper and the varnish coating, which can ensure that the varnish has good adhesion strength on the paper after application and reduce the probability of the varnish coating falling off the paper.

[0009] Optionally, the particle size of the gold sand powder is 100um.

[0010] A method for preparing the above-mentioned water-based plastic-replacing varnish comprises the following steps:

[0011] First, water-based polyurethane resin, water, and polyether-modified silicone surfactant are mixed and dispersed to obtain a mixed solution A. Water-based polypropylene wax is then added to the mixed solution A and dispersed to obtain a mixed solution B. Gold sand powder is added to the mixed solution B and then dispersed to obtain a mixed solution C. Water-based acrylic resin and water are added to the mixed solution C and dispersed.

[0012] Optionally, after the waterborne polyurethane resin, water and polyether-modified silicone surfactant are mixed, the temperature of the mixed solution is maintained at 25° C. to 30° C., and the dispersion treatment is performed by stirring and dispersing.

[0013] In this preparation method, after the waterborne polyurethane resin, water, and polyether-modified silicone surfactant are mixed, the temperature of the mixed solution is maintained at 25°C~30°C, and the dispersion is carried out by stirring, which can ensure that the reactants are fully mixed and avoid volatilization of materials during the mixing process.

[0014] Optionally, after the mixed liquid A is mixed with the aqueous acrylic wax, the temperature of the mixed liquid is maintained at 25° C. to 30° C., and the dispersion treatment is performed by stirring and dispersing.

[0015] The temperature of the mixed liquid is maintained at 25℃~30℃, and the dispersion treatment is carried out by stirring and dispersing. This can ensure that the reactants are fully mixed and avoid volatilization of materials during the mixing process.

[0016] Optionally, after the mixed solution B is mixed with the gold sand powder, the temperature of the mixed solution is maintained at 0°C~4°C, and ultrasonic dispersion is used for dispersion treatment.

[0017] After the mixed solution B is mixed with the gold sand powder, the temperature of the mixed solution is maintained at 0°C~4°C, and ultrasonic dispersion is used for dispersion treatment. Compared with stirring dispersion, ultrasonic dispersion can fully oscillate the gold sand powder, so that the gold sand powder is more evenly mixed in the mixed solution B. At the same time, since the temperature of the mixed solution is maintained at 0°C~4°C, at this temperature, the chemical reaction between the components in the solution can be reduced as much as possible under the condition of ultrasonic treatment, so as to keep the properties of the entire mixed solution stable.

[0018] Optionally, after the water-based acrylic resin and water are added to the mixed solution C, the temperature of the mixed solution is maintained at 25° C. to 30° C., and the dispersion treatment is performed by stirring and dispersing.

[0019] Optionally, the mixed solution A is alkaline, the mixed solution B is alkaline, and the mixed solution C is alkaline.

[0020] Specifically, this kind of gold sand polish uses a polyether-modified silicone surfactant, so the reaction liquid is in a weakly alkaline state during the entire preparation process, and the pH is roughly between 7 and 9.

[0021] The invention has the beneficial effects of being composed of water-based polyurethane resin, water-based acrylic resin, gold sand powder, water, water-based polypropylene wax and polyether-modified silicone surfactant, the entire component does not contain inflammable and explosive components of alcohols and ethers such as methanol, ethanol, isopropanol, isobutyl alcohol, ethyl ether, propylene glycol ethyl ether, propylene glycol methyl ether, and does not contain components harmful to the human body, and is relatively safe and reliable during use and preparation. DETAILED DESCRIPTION

[0022] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description of the specific embodiments of the present invention.

[0023] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0024] Example 1

[0025] A water-based plastic replacement gold sand polish, comprising 30-40 parts of water-based polyurethane resin, 10-30 parts of water-based acrylic resin, 10-20 parts of gold sand powder, 10-20 parts of water, 3-5 parts of water-based polypropylene wax, and 0.5-3 parts of polyether-modified organic silicon surfactant. The particle size of the gold sand powder is 100um.

[0026] Example 2

[0027] A water-based plastic replacement gold sand polish, comprising 30 parts of water-based polyurethane resin, 10 parts of water-based acrylic resin, 10 parts of gold sand powder, 10 parts of water, 3 parts of water-based polypropylene wax, and 0.5 parts of polyether-modified organic silicon surfactant. The particle size of the gold sand powder is 100um.

[0028] Example 3

[0029] A water-based plastic replacement gold sand polish, comprising 40 parts of water-based polyurethane resin, 10 parts to 30 parts of water-based acrylic resin, 10 parts to 20 parts of gold sand powder, 10 parts to 20 parts of water, 3 parts to 5 parts of water-based polypropylene wax, and 0.5 parts to 3 parts of polyether-modified organic silicon surfactant. The particle size of the gold sand powder is 100um.

[0030] Example 4

[0031] A water-based plastic replacement gold sand polish, comprising 35 parts of water-based polyurethane resin, 20 parts of water-based acrylic resin, 15 parts of gold sand powder, 15 parts of water, 4 parts of water-based polypropylene wax, and 2 parts of polyether-modified organic silicon surfactant. The particle size of the gold sand powder is 100um.

[0032] It should be noted that the parts of each component in the above Examples 1 to 4 are parts by mass.

[0033] Example 5

[0034] A method for preparing a water-based plastic-replacing varnish comprises the following steps:

[0035] 35 parts of waterborne polyurethane resin, 10 parts of water, and 2 parts of polyether-modified silicone surfactant were mixed, and the temperature of the mixed solution was maintained at 25°C to 30°C. Mixed solution A was obtained by dispersing the mixture in a dispersing machine by stirring and dispersing the mixture. The dispersing machine was operated at 800 rpm for 5 minutes.

[0036] Mixed solution A was mixed with 20 parts of aqueous acrylic wax, and the temperature of the mixed solution was maintained at 25°C to 30°C. Mixed solution B was obtained by dispersing the mixture in a dispersing machine with stirring and dispersing parameters of 1000 rpm and dispersion for 10 minutes.

[0037] Mixed solution B was mixed with 15 parts of gold sand powder, the temperature of the mixed solution was maintained at 0°C to 4°C, and ultrasonic dispersion was used to obtain mixed solution C, wherein the ultrasonic time was 4 minutes. The particle size of the gold sand powder was 100 um.

[0038] After adding 20 parts of water-based acrylic resin and 5 parts of water into the mixed solution C, the temperature of the mixed solution is maintained at 25°C to 30°C, and a dispersing machine is used for dispersion treatment, wherein the operating parameters of the dispersing machine are 1000 rpm and the dispersion time is 10 minutes.

[0039] Comparative Example 1

[0040] 35 parts of waterborne polyurethane resin, 10 parts of water, and 2 parts of polyether-modified silicone surfactant were mixed, and the temperature of the mixed solution was maintained at 25°C to 30°C. Mixed solution A was obtained by dispersing the mixture in a dispersing machine by stirring and dispersing the mixture. The dispersing machine was operated at 800 rpm for 5 minutes.

[0041] After the mixed solution A is mixed with 20% water-based acrylic wax, the temperature of the mixed solution is maintained at 25°C to 30°C, and the mixed solution B is obtained by dispersing the mixed solution in a dispersing machine by stirring and dispersing. The operating parameters of the dispersing machine are 1000 rpm and the dispersing time is 10 minutes.

[0042] Mix the mixture B with 15 parts of gold sand powder, maintain the temperature of the mixture at 0℃~4℃, and disperse it by stirring with a disperser, wherein the operating parameters of the disperser are 1000 rpm and the dispersion time is 10 minutes. The particle size of the gold sand powder is 100um.

[0043] After adding 20 parts of water-based acrylic resin and 5 parts of water into the mixed solution C, the temperature of the mixed solution is maintained at 25°C to 30°C, and a dispersing machine is used for dispersion treatment, wherein the operating parameters of the dispersing machine are 1000 rpm and the dispersion time is 10 minutes.

[0044] Comparative Example 2

[0045] 35 parts of waterborne polyurethane resin, 10 parts of water, and 2 parts of polyether-modified silicone surfactant were mixed, and the temperature of the mixed solution was maintained at 25°C to 30°C. Mixed solution A was obtained by dispersing the mixture in a dispersing machine by stirring and dispersing the mixture. The dispersing machine was operated at 800 rpm for 5 minutes.

[0046] After the mixed solution A is mixed with 20% water-based acrylic wax, the temperature of the mixed solution is maintained at 25°C to 30°C, and the mixed solution B is obtained by dispersing the mixed solution in a dispersing machine by stirring and dispersing. The operating parameters of the dispersing machine are 1000 rpm and the dispersing time is 10 minutes.

[0047] Mixed solution B was mixed with 15 parts of gold sand powder, the temperature of the mixed solution was maintained at 25°C to 30°C, and ultrasonic dispersion was used to obtain mixed solution C, wherein the ultrasonic time was 4 minutes. The particle size of the gold sand powder was 100 um.

[0048] After adding 20 parts of water-based acrylic resin and 5 parts of water into the mixed solution C, the temperature of the mixed solution is maintained at 25°C to 30°C, and a dispersing machine is used for dispersion treatment, wherein the operating parameters of the dispersing machine are 1000 rpm and the dispersion time is 10 minutes.

[0049] Comparative Example 3

[0050] Mix 35 parts of waterborne polyurethane resin, 20 parts of waterborne acrylic resin, 15 parts of gold sand powder, 15 parts of water, 4 parts of waterborne polypropylene wax and 2 parts of polyether modified silicone surfactant, maintain the temperature of the mixture at 25-30°C, and then stir and disperse in a disperser, where the operating parameters of the disperser are 1000 rpm and the operating time is 25 minutes. The particle size of the gold sand powder is 100um.

[0051] Comparative Example 4

[0052] Mix 35 parts of waterborne polyurethane resin, 20 parts of waterborne acrylic resin, 15 parts of gold sand powder, 15 parts of water, 4 parts of waterborne polypropylene wax and 2 parts of polyether modified silicone surfactant, maintain the temperature of the mixture at 25-30°C, and then stir and disperse in a disperser, where the operating parameters of the disperser are 1000 rpm and the operating time is 25 minutes. The particle size of the gold sand powder is 100um.

[0053] The varnish prepared in the above-mentioned Example 5, Control Example 1, Control Example 2, Control Example 3 and Control Example 4 is applied on coated paper. After the varnish is solidified, the wear resistance, glossiness and adhesion strength of the varnish coating on the coated paper are tested, and the bending resistance of the coated paper after the varnish is applied is tested.

[0054] The wear resistance is measured by a friction tester, the glossiness is measured by a gloss meter, the adhesion strength of the varnish layer is measured by a disc peeling method, and the bending resistance is measured by a bending resistance tester. The measurement structure is shown in the following table.

[0055] project Indicator range Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Wear resistance ≥500 times without ink loss 500 times without dropping 400 times without dropping 350 times without dropping 200 times without dropping 250 times without dropping Glossiness ≤15 15 30 25 20 35 Adhesion strength ≥95% no ink drop 100% no drop 90% not falling 80% not falling 80% not falling 850% not falling Bending resistance ≥50 times 50 times 20 times 25 times 30 times 10 times

[0056] From the data in the comprehensive table, we can know that mixing the gold sand powder into the liquid at a temperature of 0~4℃ can make the gold sand powder and varnish fully and evenly mixed. When the varnish is applied to the paper, it has good wear resistance and adhesion strength, and can improve the bending resistance of the whole paper. The reason is that the gold sand powder in this varnish is evenly distributed in the varnish and forms a suspension. After being applied to the paper and solidified, a firmly attached layer is formed on the paper.

[0057] At the same time, it can be seen from the data in the above table (i.e., Control Example 3 and Control Example 4) that the various indicators of the varnish prepared by mixing all the materials together and dispersing them at one time are relatively poor, while the various indicators of the varnish prepared by mixing the materials step by step and dispersing them by different dispersion methods in Example 5 are the best. It can be seen that the varnish prepared by distributed mixing has better performance.

[0058] The above-described embodiments only express some embodiments of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, it is still possible to modify the technical solutions recorded in the above-mentioned embodiments, or to replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A water-based plastic sand replacement varnish, characterized in that: It includes 30-40 parts of water-based polyurethane resin, 10-30 parts of water-based acrylic resin, 10-20 parts of gold sand powder, 10-20 parts of water, 3-5 parts of water-based polypropylene wax, and 0.5-3 parts of polyether modified silicone surfactant.

2. A water-based plastic sand replacement polish according to claim 1, characterized in that: The particle size of the gold sand powder is 100um.

3. A method for preparing an aqueous plastic replacement polish as claimed in any one of claims 1 to 2, characterized in that: The following steps are included: First, water-based polyurethane resin, water, and polyether-modified silicone surfactant are mixed and dispersed to obtain a mixed solution A. Water-based polypropylene wax is then added to the mixed solution A and dispersed to obtain a mixed solution B. Gold sand powder is added to the mixed solution B and then dispersed to obtain a mixed solution C. Water-based acrylic resin and water are added to the mixed solution C and dispersed.

4. The preparation method according to claim 3, characterized in that: After the waterborne polyurethane resin, water and polyether-modified silicone surfactant are mixed, the temperature of the mixed solution is maintained at 25° C. to 30° C., and the dispersion treatment is performed by stirring and dispersing.

5. The preparation method according to claim 3, characterized in that: After the mixed liquid A is mixed with the water-based acrylic wax, the temperature of the mixed liquid is maintained at 25° C. to 30° C., and a stirring dispersion method is used for dispersion treatment.

6. The preparation method according to claim 3, characterized in that: After the mixed solution B is mixed with the gold sand powder, the temperature of the mixed solution is maintained at 0°C~4°C, and ultrasonic dispersion is used for dispersion treatment.

7. The preparation method according to claim 3, characterized in that: After the water-based acrylic resin and water are added to the mixed solution C, the temperature of the mixed solution is maintained at 25° C. to 30° C., and the dispersion treatment is performed by stirring and dispersing.

8. The preparation method according to claim 3, characterized in that: The mixed solution A is alkaline, the mixed solution B is alkaline, and the mixed solution C is alkaline.

Citation Information

Patent Citations

  • Water-based buffing oil for paper

    CN101725082B

  • Water-based plastic-replacing oil and preparation method thereof

    CN113278352A

  • Aluminum-free antibacterial lined paper

    CN202786966U

Cited By

  • Printed gold sand effect composite film

    CN224766240U